London and the Spectre of Anarchy: Chesterton's The Man Who Was Thursday as Urban History. Issue 3 (3rd July 2021) - Gulliver, Katrina
Summary: This article discusses how the criminal threat of anarchist attack was treated in G.K. Chesterton's novel, The Man Who Was Thursday. The novel captures a particular moment of public concern about terrorism and serves as an object of cultural history in its depiction of London as a den of crime. The plot focuses on an undercover policeman who infiltrates a terror cell. The kind of terrorism depicted was a real threat, yet Chesterton parodied both the aspirations of anarchists, and the anti-terror efforts of law enforcement. This article considers the historical background of anarchism and how the history of the city is part of the novel's framework.